Lipid-based nutrient supplements and all-cause mortality in children 6–24 months of age: A meta-analysis of randomized controlled trials - Stewart, Christine P.; Wessells, K. Ryan; Arnold, Charles D.; Huybregts, Lieven; Ashorn, Per; Becquey, Elodie (Oxford University Press, 2020)
Background: Undernutrition is associated with an elevated risk of mortality among children in low- and middle-income countries. Small-quantity lipid-based nutrient supplements (LNS) have been evaluated as a method to prevent undernutrition and improve infant development, but the effects on mortality are unknown.